2014
DOI: 10.1088/0953-2048/27/4/044009
|View full text |Cite
|
Sign up to set email alerts
|

Critical current anisotropy in Nd-1111 single crystals and the influence of neutron irradiation

Abstract: We report on angle-resolved magnetization measurements on NdFeAsO 0.65 F 0.35 (Nd-1111) single crystals. The field dependence of the critical current density, J c , is non-monotonous in these crystals at all orientations and temperatures due to the fishtail effect, which strongly influences the angular dependence of J c . The currents decrease as the field is tilted from the crystallographic c-axis at low fields, but increase at high fields. A peak occurs in the angular dependence of J c at intermediate fields… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
(136 reference statements)
0
6
1
Order By: Relevance
“…(c) Fe(Se,Te) on Fe-buffered MgO prepared by PLD23 and Fe 1+y Te 0.6 Se 0.4 single crystal 24. (d) NdFeAs(O,F) on MgO fabricated by MBE 25 and single crystal 26.…”
mentioning
confidence: 99%
“…(c) Fe(Se,Te) on Fe-buffered MgO prepared by PLD23 and Fe 1+y Te 0.6 Se 0.4 single crystal 24. (d) NdFeAs(O,F) on MgO fabricated by MBE 25 and single crystal 26.…”
mentioning
confidence: 99%
“…6(b) and 6(c), respectively. We note that the estimated critical current densities, jc, are slightly lower than those of single-crystalline iron-pnictide superconductors with Tc ~ 40 K [55,56]. This is not surprising, considering that, the upper-and the lower critical fields of our crystals are smaller than those of the iron-pnictide counterparts and that the pinning is proportional to the thermodynamic critical fields.…”
Section: The Critical Current Densitymentioning
confidence: 56%
“…The B * c2 anisotropy in figure 10 is of particular importance. For a number of iron-based superconductors, namely NdFeAsO 0.65 F 0.35 (Nd-1111) [81], LaFeAsO 1−x F x (La-1111) [58], Ba(Fe 1−x Co x ) 2 As 2 (Ba-122) [82], and Fe(Se,Te) (11) [83], it was shown that the single-band scaling approach by Blatter et al [84] properly describes the angular dependences B * c2 (ϑ), B c2 (ϑ), and j c (ϑ) also for a multiband system. When ϑ is the angle that makes the applied field B with the c-axis (ϑ = 0 • for B II c and ϑ = 90 • for B II ab), B * c2 (ϑ) is related to the ratio of the effective masses of the effective charge carriers m c along the c-axis and m ab in the ab-plane through the equation…”
Section: Effective-mass Anisotropymentioning
confidence: 99%